Swedish student nurses' perception of peer learning as an educational model during clinical practice in a hospital setting—an evaluation study. Issue 1 (December 2015) - Stenberg, Marie; Carlson, Elisabeth
Abstract Background Peer learning, a collaborative learning model has no tradition in clinical education for undergraduate student nurses in Sweden, and little is reported of the student experience. An increasing number of students have led to a pressing need for preceptors and clinical placements thus, highlighting the need for a supportive educational model. The objectives for the current study were to explore how student nurses' evaluated peer learning as an educational model during clinical practice in a hospital setting, and to compare perceptions among student nurses from year one and three. Methods A questionnaire developed for the purpose of this study was developed and responded to by 62 (year one) and 73 (year three) student nurses. Data were collected between 2011 and 2013. The questionnaire contained six open- ended and eight closed questions on a four point Likert-scale. Written responses were analysed by content analysis and the closed questions by using descriptive statistics. Mann–Whitney U-test was used to examine differences in relation to students from year one and three. Results The peer learning experience was evaluated in a positive way. Statistical significance differences were shown for two out of eight closed questions. The peer learning activities were evaluated as supportive and relevant for learning. Three categories emerged from the content analysis: "a feeling of safety", "a sense of competition" and "the learning experience". Conclusion A feeling of safety seems to be connected to students' perception of increased learning and independence. However, the sense of negative competition needs to be addressed when students are prepared for the teaching and learning activities in the peer learning model. Finally, what needs to be further investigated is what challenges and opportunities the peer learning model presents to preceptors.